2022
DOI: 10.1016/j.jbc.2021.101413
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and in vivo phenotyping of missense variants of the human glucagon receptor

Abstract: Naturally occurring missense variants of G protein–coupled receptors with loss of function have been linked to metabolic disease in case studies and in animal experiments. The glucagon receptor, one such G protein–coupled receptor, is involved in maintaining blood glucose and amino acid homeostasis; however, loss-of-function mutations of this receptor have not been systematically characterized. Here, we observed fewer glucagon receptor missense variants than expected, as well as lower allele diversity and fewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 88 publications
1
17
0
Order By: Relevance
“…Furthermore, this genetic variant in GIPR has been reported to be associated with increased plasma levels of GIP as well as various anthropometric and glycemic traits 38 . The p.G40S variant in GCGR has been reported to impair signaling through β-arrestin-1 23 . This p.G40S variant in GCGR has been reported to be associated with diabetes 22 , but this finding seems not to be reproducible 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this genetic variant in GIPR has been reported to be associated with increased plasma levels of GIP as well as various anthropometric and glycemic traits 38 . The p.G40S variant in GCGR has been reported to impair signaling through β-arrestin-1 23 . This p.G40S variant in GCGR has been reported to be associated with diabetes 22 , but this finding seems not to be reproducible 39 .…”
Section: Discussionmentioning
confidence: 99%
“…This pilot study was designed to test the hypothesis that missense variants in two candidate genes (GCGR and GIPR) might be associated with pharmacodynamic responses to GLP1 receptor agonists. Table S3 compares pharmacodynamic responses to exenatide among three groups of people: (a) individuals who are homozygous for the major alleles of both genes; (b) homozygotes for the G40S variant of GCGR (rs1801483) 22,23 ; and (c) homozygotes for the E354Q variant of GIPR (rs1800437) [24][25][26] (Table S3). Four co-primary endpoints were prespecified: association of genotype (either G40S-GCGR or E354Q-GIPR) with the magnitude of drug effect (i.e., either exenatide-induced augmentation of first phase insulin secretion or exenatide-induced acceleration of the rate of glucose disappearance).…”
Section: Effect Of Genotypementioning
confidence: 99%
“…This pilot study was designed to test the hypothesis that missense variants in two candidate genes (GCGR and GIPR) might be associated with pharmacodynamic responses to GLP-1R agonists. Table S3 compares pharmacodynamic responses to exenatide among three groups of people: (a) individuals who are homozygous for the major alleles of both genes; (b) homozygotes for the G40S variant of GCGR (rs1801483) 11,19 ; and (c) homozygotes for the E354Q variant of GIPR (rs1800437) 10,20,21 (Table S3). Four co-primary endpoints were prespecified: association of genotype (either G40S-GCGR or E354Q-GIPR) with the magnitude of drug effect (i.e.…”
Section: Effect Of Genotypementioning
confidence: 99%
“…We focused on two variants (rs1800437 and rs850763), which have been reported to alter the function of GIPR and GCGR, respectively. 10,11 2 | METHODS…”
Section: Introductionmentioning
confidence: 99%
“…For example, in addition to Gly40Ser, homozygous missense mutations (P86S) have been found in GCGR ; these mutations contribute to the formation of an ineffective GCGR, resulting in hyperglycemia and extreme α-cell proliferation ( 65 ). Recent studies have reported 250 missense variants in human GCGR ( 66 , 67 ). GCGR shows lower allelic diversity and fewer missense variants and variants with trait associations than the other class B1 GPCRs.…”
Section: Association Of Gcgr Mutations With Diabet...mentioning
confidence: 99%